The molecular etiology and treatment of glucocorticoid-induced osteoporosis - Cheng-Huan Peng; Wen-Ying Lin; Kuang-Ting Yeh; Ing-Ho Chen; Wen-Tien Wu; Ming-Der Lin (Tzu Chi Medical Journal)
Glucocorticoid-induced osteoporosis (GIOP) is the most common form of secondary osteoporosis, accounting for 20% of osteoporosis diagnoses. Using glucocorticoids for >6 months leads to osteoporosis in 50% of patients, resulting in an increased risk of fracture and death. Osteoblasts, osteocytes, and osteoclasts work together to maintain bone homeostasis. When bone formation and resorption are out of balance, abnormalities in bone structure or function may occur. Excess glucocorticoids disrupt the bone homeostasis by promoting osteoclast formation and prolonging osteoclasts' lifespan, leading to an increase in bone resorption. On the other hand, glucocorticoids inhibit osteoblasts' formation and facilitate apoptosis of osteoblasts and osteocytes, resulting in a reduction of bone formation. Several signaling pathways, signaling modulators, endocrines, and cytokines are involved in the molecular etiology of GIOP. Clinically, adults ≥40 years of age using glucocorticoids chronically with a high fracture risk are considered to have medical intervention. In addition to vitamin D and calcium tablet supplementations, the major therapeutic options approved for GIOP treatment include antiresorption drug bisphosphonates, parathyroid hormone N-terminal fragment teriparatide, and the monoclonal antibody denosumab. The selective estrogen receptor modulator can only be used under specific condition for postmenopausal women who have GIOP but fail to the regular GIOP treatment or have specific therapeutic contraindications. In this review, we focus on the molecular etiology of GIOP and the molecular pharmacology of the therapeutic drugs used for GIOP treatment.